The COVID-19 Crisis and Telework: A Research Survey on Experiences, Expectations and Hopes - Stijn Baert; Louis Lippens; Eline Moens; Philippe Sterkens; Johannes Weytjens (Institute of Labor Economics (IZA), 2020)
While a considerable number of employees across the globe are being forced to work from home due to the COVID-19 crisis, it is a guessing game as to how they are experiencing this current surge in telework. Therefore, we examined employee perceptions of telework on various life and career aspects, distinguishing between typical and extended telework during the COVID-19 crisis. To this end, we conducted a state-of-the-art web survey among Flemish employees. Notwithstanding this exceptional time of sudden, obligatory and high-intensity telework, our respondents mainly attribute positive characteristics to teleworking, such as increased efficiency and a lower risk of burnout. The results also suggest that the overwhelming majority of the surveyed employees believe that teleworking (85%) and digital conferencing (81%) are here to stay. In contrast, some fear that telework diminishes their promotion opportunities and weakens ties with their colleagues and employer.
Keywords: J22; J28; D24; I10; J15; J24; 330; videoconferencing; telework; COVID-19; career